TEACHING METHOD THROUGH GROUP WORK TO IMPROVE VOCABULARY OF THE SEVENTH GRADE STUDENTS OF SMP WAHYU MAKASSAR - Satriana Satriana (Teaching English as a Foreign Language Overseas Journal, 2022)
Background of this research is students’ motivation still low in learning English, it is caused by method which is not interested in teaching and learning process. The aim of this research is to know the effect of Teaching Method through Group Work to Improve Vocabulary of the Students SMP Wahyu Makassar. This research used classroom action research (CAR) method. The populations are class VII of SMP Wahyu Makassar that consist of 5 classes. Every class consist of 20 students, meanwhile the population are 170 students. The sample of this research are 20 students of class VII-D (only one class). The instrument that uses in this research is test (multiple choices). The data analysis result show that there is significant difference of the student’s vocabulary mastery after taught using group work method. It shows at significant statistic level data analysis result. Based on the analysis result, the writer concluded that the use of group work method can improve students’ vocabulary mastery and students have very high motivation in learning English by using group work method.